2013
DOI: 10.1186/1129-2377-14-97
|View full text |Cite
|
Sign up to set email alerts
|

Migraine misdiagnosis as a sinusitis, a delay that can last for many years

Abstract: BackgroundSinusitis is the most frequent misdiagnosis given to patients with migraine.Therefore we decided to estimate the frequency of misdiagnosis of sinusitis among migraine patients.MethodsThe study included migraine patients with a past history of sinusitis. All included cases fulfilled the International Classification of Headache Disorders, 3rd edition (ICHD-III- beta) criteria. We excluded patients with evidence of sinusitis within the past 6 months of evaluation. Demographic data, headache history, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 19 publications
2
26
1
1
Order By: Relevance
“…38 Similarly, neck pain may be a comorbidity of migraine if it has an independent etiology, or a manifestation of migraine if pain is referred to the upper cervical nerve routes. In some cases, apparent comorbid conditions may be manifestations of migraine per se.…”
Section: Discussionmentioning
confidence: 99%
“…38 Similarly, neck pain may be a comorbidity of migraine if it has an independent etiology, or a manifestation of migraine if pain is referred to the upper cervical nerve routes. In some cases, apparent comorbid conditions may be manifestations of migraine per se.…”
Section: Discussionmentioning
confidence: 99%
“…A special attention should be given to cervicogenic headache and sinus headache for which CM is often misdiagnosed [17]. For the diagnosis of cervicogenic headache, evidence is needed that a disorder within the cervical spine or soft tissues of the neck, known to be able to cause headache, is present, as well as proof of a causal relation by temporal association, provocative manoeuvres or a diagnostic blockade [3].…”
Section: Differential Diagnosis Of Chronic Migrainementioning
confidence: 99%
“…1 However, a majority of physician-and/or patientdiagnosed "sinus headache" has in numerous studies been demonstrated to meet diagnostic criteria for migraine and respond to migraine-specific medications. 6,7 In the Sinus, Allergy, and Migraine Study (SAMS), more than half (52%) of 100 consecutively consulting patients believed they had sinus headache, but the results determined they had migraine with or without aura, and 23% had probable migraine. 8 In another study of 2991 patients with a history of selfdescribed or physician-diagnosed "sinus" headache and no previous diagnosis of migraine, 80% met International Headache Society (IHS) criteria for migraine without or with aura, and 8% met IHS criteria for migrainous headache.…”
Section: Anatomy Of Facial Painmentioning
confidence: 99%
“…Various studies have shown that when patients self-report their headaches as "sinus" in origin, physicians are more likely to agree with the diagnosis. 6,7 The lay term of "sinus headache" continues to be perpetuated in the media. Primary care physicians and patients alike appear to continue to prefer the choice of "sinus headache" as the medical term when patients experience facial pain or pressure À symptoms traditionally associated with sinus disease.…”
Section: Sinus Headachementioning
confidence: 99%